2017
DOI: 10.1037/dev0000277
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent support seeking as a path to adult functional independence.

Abstract: The potential importance of depending on others during adolescence in order to establish independence in young adulthood was examined across adolescence to emerging adulthood. Participants included 184 teens (46% male; 42% non-White), their mothers, best friends, and romantic partners, assessed at ages 13–14, 18, 21–22, and 25. Path analyses showed that associations were both partner and age specific: markers of independence were predicted by participants’ efforts to seek support from mothers at age 13, best f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 62 publications
1
32
0
Order By: Relevance
“…In one exception, there was a positive correlation between adult functional independence and job competence among young adults. Moreover, adult functional independence among these young adults was positively correlated with highest level of education attained and current employment status, suggesting that adult functional competence may indeed be relevant as a predictor of career satisfaction (Szwedo, Hessel, Loeb, Hafen, & Allen, 2017). There is also indirect evidence that such competence might be associated with both anxiety and career outcomes provided by research examining related constructs.…”
Section: Positive Coping Skills and Adult Functional Competencementioning
confidence: 99%
“…In one exception, there was a positive correlation between adult functional independence and job competence among young adults. Moreover, adult functional independence among these young adults was positively correlated with highest level of education attained and current employment status, suggesting that adult functional competence may indeed be relevant as a predictor of career satisfaction (Szwedo, Hessel, Loeb, Hafen, & Allen, 2017). There is also indirect evidence that such competence might be associated with both anxiety and career outcomes provided by research examining related constructs.…”
Section: Positive Coping Skills and Adult Functional Competencementioning
confidence: 99%
“…The process of developing attachment occurs over a period of time and is not automatic or immediate (Bowlby, ). Attachment relationships can have positive and negative characteristics, and perceived security or support in a parent–child relationship affects both the tone and the trajectory for future relationships (Szwedo et al, ).…”
Section: Emerging Adulthoodmentioning
confidence: 99%
“…Additionally, perceived competence in the transition to adulthood was positively related to peer friendship quality for women (Haydon, ), and Kawamoto () showed that peer attachment relationships shape social identity during EA. Szwedo et al () suggested that individuals in EA tend to seek support from best friends rather than parents at age 18, but emerging adults’ ability to seek support from friends may be influenced by parental support. As with parent attachment, peer attachment is expressed through varying levels of trust, communication, and closeness (Armsden & Greenberg, ; Jiang et al, ).…”
Section: Emerging Adulthoodmentioning
confidence: 99%
See 1 more Smart Citation
“…As far as possible, please keep the introduction comprehensible to scientists outside your particular field of research. References should be numbered in order of appearance and indicated by a numeral or numerals in square brackets, e.g., [1] or [2,3], or [4][5][6]. See the end of the document for further details on references.…”
Section: Introductionmentioning
confidence: 99%